Inhibition of Amyloid-Beta Production, Associated Neuroinflammation, and Histone Deacetylase 2-Mediated Epigenetic Modifications Prevent Neuropathology in Alzheimer’s Disease in vitro Model - Atluri, Venkata Subba Rao; Tiwari, Sneham; Rodriguez, Melisa; Kaushik, Ajeet; Yndart, Adriana; Kolishetti, Nagesh; Yatham, Mohan; Nair, Madhavan (Frontiers in Aging Neuroscience, 2020)
Alzheimer’s disease (AD) is a growing global threat to healthcare in the aging population. In the USA alone, it is estimated that one in nine persons over the age of 65 years is living with AD. The pathology is marked by the accumulation of amyloid-beta (Aβ) deposition in the brain, which is further enhanced by the neuroinflammatory process. Nucleotide-binding oligomerization domain, leucine rich repeat and pyrin domain containing 3 (NLRP3) and nuclear factor kappa-light-chain-enhancer of activated B cells (NF-κB) are the major neuroinflammatory pathways that intensify AD pathogenesis. Histone deacetylase 2 (HDAC2)-mediated epigenetic mechanisms play a major role in the genesis and neuropathology of AD. Therefore, therapeutic drugs, which can target Aβ production, NLRP3 activation, and HDAC2 levels, may play a major role in reducing Aβ levels and the prevention of associated neuropathology of AD. In this study, we demonstrate that withaferin A (WA), an extract from Withania somnifera plant, significantly inhibits the Aβ production and NF-κB associated neuroinflammatory molecules’ gene expression. Furthermore, we demonstrate that cytokine release inhibitory drug 3 (CRID3), an inhibitor of NLRP3, significantly prevents inflammasome-mediated gene expression in our in vitro AD model system. We have also observed that mithramycin A (MTM), an HDAC2 inhibitor, significantly upregulated the synaptic plasticity gene expression and downregulated HDAC2 in SH-SY5Y cells overexpressing amyloid precursor protein (SH-APP cells). Therefore, the introduction of these agents targeting Aβ production, NLRP3-mediated neuroinflammation, and HDAC2 levels will have a translational significance in the prevention of neuroinflammation and associated neurodegeneration in AD patients.